EFEKTIVITAS KINERJA APARATUR SIPIL NEGARA DALAM PELAYANAN PUBLIK DI MASA PANDEMIC COVID-19 - Alifbata Sarel Andra Jihad Panghegar; Muhammad Eko Atmojo (Jurnal Pemerintahan dan Kebijakan (JPK), 2021)
This study aims to determine the effectiveness of the performance of the State Civil Servants of the Sleman Regency Population and Civil Registration Service in serving the community during the Covid-19 pandemic. This research is presented by the author using a qualitative approach. The analysis used by the author includes, data collection, data reduction, data presentation, and concluding. The results of this study indicate that in its implementation, the performance of ASN at the Department of Population and Civil Registration of Sleman Regency is based on indicators such as adaptability, work performance, and work ability. The existence of the Covid-19 pandemic has not had a major effect on performance, it affects the service mechanism that implements health protocols such as maintaining distance, wearing masks, limiting the number of people who take care of population administration. In addition, the Department of Population and Civil Registration of Sleman Regency also implements an online service system, but the existence of this online service, according to the expressions of some of the community, this service cannot be fully relied upon because to process documents still have to come and wait a long time.